Internet banking adoption: an empirical study - Al-Ajam, Ali Saleh (2013)
Rejection of Internet banking is one of the most important problems that faces banks in developing countries. So far, very few academic studies have been conducted on internet banking adoption in Arab countries. Hence, this research aims to investigate factors that influence the behavioral intention to use Internet banking in Yemen. Cross-sectional data were collected from 1286 respondents through a survey. Data were then analyzed by structural equation modeling. The findings verified the research hypotheses and confirmed that perceived relative advantages and perceived ease of use, all impact attitude toward the intention of adopting Internet banking. This paper makes a contribution to Internet banking literature by providing insights on the factors that affect Internet banking adoption. The results hint that information about Internet banking services, and its benefits is a critical factor influencing the adoption of Internet banking service. The findings made a contribution in terms of understanding the factors that can contribute to the adoption of Internet banking by Yemeni consumers.